Preliminary phytochemical screening of eurycomanone for selection of high quality planting materials: Eurycoma longifolia - Mohd Zaki, A.; Nor Fadilah, W.; Mohd Radzi, A.; Sui, Kiong L.; Ab. Rasip, A.G.; Mohamad Lokmal, N.; Abdul Rashid, L.; Ahmad Fauzi, M.S.; Farah Fazwa, M.A.; Regina Mariah, J. (Penerbit Universiti Kebangsaan Malaysia, 2015)
Eurycoma longifolia has been widely used in traditional herbal preparation and presently there are many commercial products available for general health and libido. However, study on plant breeding of this species is still in its infancy. Thus, Forest Research Institute Malaysia (FRIM) has taken an initiative to conduct provenance trial of this species in order to select the best provenance and eurycomanone is chosen as bioactive marker. The aim of this study was to analyze the percentage of eurycomanone extracted from root, stem and leaves parts of E. longifolia from different provenances collected throughout Peninsular Malaysia. The eurycomanone compound is extracted with pure water and the present is detected by Ultra Performance Liquid Chromatography (UPLC). Findings showed that the highest percentage of eurycomanone present in the root extract of Terengganu with 1.46% while the lowest is Melaka with 0.17%. Stem part of the plant showed there was presence of eurycomanone compound relatively in small percentage except for Terengganu, while there was no eurycomanone compound detected in leaves extract from all provenances tested (Johor, Kedah/Perlis, Melaka, Pahang, Perak, Pulau Pinang, Selangor and Terengganu). However, it is still too early to derive any conclusion on the best provenance based on chemical marker itself.